The role of governance in realising the transition towards sustainable societies. (1st February 2016) - Leal Filho, Walter; Platje, Joost; Gerstlberger, Wolfgang; Ciegis, Remigijus; Kääriä, Juha; Klavins, Maris; Kliucininkas, Linas
Abstract: It is widely known that governance is central to the successful implementation of sustainable development policies and measures. Yet, there is a paucity of research which explore the links between governance and sustainability. This paper attempts to address this research need by providing an analysis of the role of governance in enabling – and to some extent – fostering a transition towards sustainable societies. A set of indicators for assessing the capacity for and willingness and commitment to transition to a more sustainable society is presented, enabling identification of direction of change. This paper presents the results of a study, in the context of which sustainability governance has been comparatively investigated in a sample of European countries with, by methodological purpose, very different economic, environmental, political and social conditions (Denmark, Finland, Germany, Latvia, Lithuania and Poland). Lessons learnt and examples of good practice – which may be replicable elsewhere-are outlined. For instance, it is discussed that limited knowledge about sustainable development amongst municipal development planners and decision-makers, deficiencies in policy integration, intersectoral cooperation, municipality and stakeholder cooperation and urban management practices are major reasons for weak governance practices in sustainable development. Furthermore, some recommendations on the role of sustainability governance are made, so as to allow the integration of the principles of governance into sustainability practice and hence provide a more general basis upon which a transition towards sustainable societies may become a reality in different types of European countries and societies. The scientific value of this paper lies in identifying opportunities for integrating principles of governance into sustainability practice, as well as outlining the basis for sustainability transitions, providing a general picture of required policy measures. The paper offers a unique comparative analysis of sustainability governance in the Baltic Sea countries, outlining some of the challenges in sustainability governance in the Baltic Sea region. Highlights: Sustainability governance is a condition for transition to a more sustainable society. It is necessary to identify opportunities for integrating principles of governance into sustainability practice. There are many challenges in sustainability governance in the Baltic Sea region. Governance for sustainability is an important factor in transitions towards sustainable societies.